2015
DOI: 10.1111/jcpt.12253
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical interventions in antiretroviral therapy: systematic review and meta-analysis of randomized clinical trials

Abstract: The results suggest that pharmaceutical interventions might contribute to improved adherence to ART and the achievement of virologic suppression, although the differences between the intervention and control groups were not statistically significant. Pharmaceutical interventions might be more efficacious in populations with low adherence to treatment and greater vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These outcomes include ART adherence, viral load suppression, reductions in the use of medical resources (hospitalization, doctor's visits, number of hospital days, visits to the emergency department), and pill burden and inappropriate discontinuation of outpatient medications as well as improved inpatient documentation of medication at home and accuracy of ART dosing. 9 The traditional pharmaceutical care model includes a large number of recommendations by pharmacists, which have typically been accepted by the doctor or health care team. Traditional standard of care for HIV patients was based on providing pharmaceutical care at the beginnings or at treatment discontinuation, the identification of drugrelated problem, and the enhancement of adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These outcomes include ART adherence, viral load suppression, reductions in the use of medical resources (hospitalization, doctor's visits, number of hospital days, visits to the emergency department), and pill burden and inappropriate discontinuation of outpatient medications as well as improved inpatient documentation of medication at home and accuracy of ART dosing. 9 The traditional pharmaceutical care model includes a large number of recommendations by pharmacists, which have typically been accepted by the doctor or health care team. Traditional standard of care for HIV patients was based on providing pharmaceutical care at the beginnings or at treatment discontinuation, the identification of drugrelated problem, and the enhancement of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes include ART adherence, viral load suppression, reductions in the use of medical resources (hospitalization, doctor’s visits, number of hospital days, visits to the emergency department), and pill burden and inappropriate discontinuation of outpatient medications as well as improved inpatient documentation of medication at home and accuracy of ART dosing. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists and other health professionals have similar consultation approaches which tend to vary during follow up. Many studies have suggested that by incorporating pharmacist in the multidisciplinary care, adherence to ART can be improved and virological suppression achieved [ 20 ]. Additionally, pharmacist-led interventions also incur some cost savings in terms of ART adherence treatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies [146][147][148] have shown significant gains in the level of adherence and clinical response of patients participating in dedicated pharmaceutical care programs. Furthermore, a recent meta-analysis [161] that evaluated four randomized controlled trials indicated that improvements in ART adherence and treatment efficacy may be greater in populations with ini-tially lower adherence and greater vulnerability, when these patients participate in pharmaceutical care interventions. Considering this evidence, the implementation of pharmaceutical care programs that include adherence evaluation and long-term personalized care is essential to increasing adherence to ART and improving patient outcomes.…”
Section: Promotion Of Adherence In Artmentioning
confidence: 99%